Imaging individual chains and aggregates on conjugated polymer films - Kemerink, Martijn; Duren, Jeroen Karolus Johannes van; Jonkheijm, Pascal; Koenraad, Paulus M.; Janssen, René A. J.; Salemink, Huub W.; Wolter, Joachim H. (MRS online proceedings library, 2003)
We demonstrate a novel method to visualize individual molecular chains in the surface layer of organic semiconducting polymer films of arbitrary thickness. The method is based on scanning force microscopy and employs a combination of a sensitive phase detection system and metal coated tips with a low (∼1 N/m) spring constant and a relatively high Q factor (∼200). The molecularly resolved morphology is observed in phase images that are taken simultaneously with the topography. Surprisingly, we found that, when the tip apex radius exceeds the intermolecular spacing in the surface layer, surface aggregates -when present- are visualized. In both cases, the phase contrast is shown to result from van der Waals interaction between the conjugated backbone of the polymer chains and the metallic tip, and can quantitatively be described by a simple harmonic oscillator model. We have employed this method to study the morphology of poly(p-phenylene vinylene) (PPV) derivatives with different substitutions.
Gesehen am 16.12.2019